(untitled) (Journal of Comilla Medical College Teachers’ Association, 2024)
Background: Hepatitis B virus (HBV) infection is the global public health challenge. Family members of the HBV infected patients have a high risk of exposure to many blood-borne diseases including Hepatitis B and Hepatitis C viral infections. Of these Hepatitis B is not only the most transmissible infection, but also the only one (HBV) that is preventable by vaccination. Objectives: To assess Occurrence of Hepatitis B Virus Infection in family contacts of HBsAg positive subject. Methods: A six-month cross sectional study was carried out at the department of Medicine, Comilla Medical College. Ethical approval from the institutional review board was obtained to ensure patient privacy and confidentiality. Results: Among 120 selected patients analysis of relatives with the infected patients revealed that most were son and daughters. In the study, out of 379 family members 316(83%) attended the study and 63 (17%) family members were unattended. Among attended family members 37 (11.7%) were known to be positive for HBV, 279 (88.3%) were found negative. Among the study subjects 68 (56.3%) were female and rest 52 (43.8%) were male. Female to male ratio was 1.28:1. Occupation of the study subjects where most were housewives (22.2%) and students (55%). Total 120 index cases, 15 (12.5%) cases were found positive family history for HBV, 90 (75%) were found negative and 15 (12.5%) were unaware of their all family members HBsAg status. Conclusion: Family members staying same house of the HBV infected patients are at highest risk. Total 15(12.5%) index cases were found positive family for HBV infection. So they should take proper preventive measures. J Com Med Col Teachers Asso Jan 2024; 28(1): 14-18